Effectiveness of Vitamin A in Albendazole Against Reinfection of Ascaris Lumbricoides - Wijaya, Richo; Lubis, Munar; Nafianti, Selfi; Lubis, Inke Nadia (Talenta Publisher, 2019)
WHO recommends the supplementation of 200,000 IU vitamin A into 400 mg albendazole to cut down its reinfection. A Randomized Controlled Trial was conducted in SD N 384 Sikapas, North Sumatera from April - June 2016. Inclusion criteria were children with ascariasis. Sample divided into intervention and control group. Kato-Katz was used to identify egg worms and faecal egg count intensity (FECs). P value < 0.05 was consider significant. After three months follow up, there were 51 and 56 samples in intervention and control group with average age 9.6 years (SD 1.99) and 9.7 years (SD 2.20). Prevalence of ascariasis was 75.5%. There was no significant difference in Ascaris lumbricoides reinfection but instead of in FECs intensity. The NNT was 22.31. The addition of vitamin A in albendazole was not suggested according to this study.